The role of Islamic human value and personal branding for success career in millennial Muslim generation / Salsya Vivi Feronica Althof and Olivia Fachrunnisa - Althof, Salsya Vivi Feronica; Fachrunnisa, Olivia (2022)
Career success is very important for the millennial generation, especially for the Muslim millennial generation. Millennials are very aware of the use of social media because they live in a faster technological development than previous generations. The magnitude of the effect of technology makes all kinds of values will affect the Muslim millennial generation, positive and negative values. In achieving career success, a generation of Muslim millennials, must have Islamic values in themselves. Having Islamic values help the development of personal branding in the millennial generation because it is considered to have more value than other individuals, it will also help in achieving careers that will be pursued, especially their career success. By using social media wisely, it helps millennial generation individuals develop their branding, of course, in balance with Islamic human values as the millennial Muslim generation. This study aims to examine the effect of Social Media Usage and Islamic Human Values on Personal Branding in Achieving Career Success in the Muslim Millennial Generation. The data from this study comes from 150 millennial Muslim generations at an Islamic Private University in Semarang, Indonesia and there are two stages in this research, the first is qualitative conducting interviews and observations and the second is quantitative. A total of 140 usable surveys were analysed. The results showed that the use of social media and Islamic human values had a positive and significant effect on personal branding. Meanwhile, personal branding has a significant positive effect on career success.